On the Origin of Raman Activity in Anatase TiO2 (Nano)Materials: An Ab Initio Investigation of Surface and Size Effects - Beata Taudul; Frederik Tielens; Monica Calatayud (Nanomaterials, 2023)
Titania-based materials are abundant in technological applications, as well as everyday products; however, many of its structure–property relationships are still unclear. In particular, its surface reactivity on the nanoscale has important consequences for fields such as nanotoxicity or (photo)catalysis. Raman spectroscopy has been used to characterize titania-based (nano)material surfaces, mainly based on empirical peak assignments. In the present work, we address the structural features responsible for the Raman spectra of pure, stoichiometric TiO2 materials from a theoretical characterization. We determine a computational protocol to obtain accurate Raman response in a series of anatase TiO2 models, namely, the bulk and three low-index terminations by periodic ab initio approaches. The origin of the Raman peaks is thoroughly analyzed and the structure–Raman mapping is performed to account for structural distortions, laser and temperature effects, surface orientation, and size. We address the appropriateness of previous experimental use of Raman to quantify the presence of distinct TiO2 terminations, and provide guidelines to exploit the Raman spectrum based on accurate rooted calculations that could be used to characterize a variety of titania systems (e.g., single crystals, commercial catalysts, thin layered materials, facetted nanoparticles, etc.).